The influence of cognitive ability on students' mathematical literacy errors: A systematic literature review - Dea Fitriyani; Iik Nurhikmayati; Olansile Samad Olalekan (Universitas Sarjanawiyata Tamansiswa, 2026)
Students’ cognitive ability influences how they comprehend, process, and represent mathematical information, which in turn affects their mathematical literacy performance. This study aims to analyze the influence of cognitive ability on students’ mathematical literacy errors through a Systematic Literature Review (SLR) using the PRISMA framework. From 500 identified articles published between 2021 and 2025, 10 studies met the inclusion criteria and were analyzed using descriptive and thematic analysis. The findings indicate that cognitive characteristics such as field-independent, reflective, and intuitive thinking are associated with better mathematical literacy performance, while field-dependent and impulsive learners tend to experience errors in understanding context, transforming information, and drawing conclusions. The reviewed studies also show that students with stronger analytical cognitive profiles consistently demonstrate fewer mathematical literacy errors. However, most existing studies are qualitative in nature, highlighting the need for more quantitative and mixed-method research to strengthen empirical evidence. This study emphasizes the importance of aligning instructional strategies with students’ cognitive characteristics to reduce errors and improve mathematical literacy. Overall, this review provides insights into how cognitive ability influences mathematical literacy errors and offers implications for adaptive mathematics instruction. This review contributes to mathematics education research by providing an integrated synthesis of cognitive characteristics associated with students’ mathematical literacy errors and identifying directions for cognitively responsive instruction and future empirical research.